Evaluation of Anthelmintic activity of Bauhinia variegata Linn Methanolic Root Extract on Pheretima posthuma - Rahul; A Jain (Current Research in Pharmaceutical Sciences, 2022)
Methanolic extracts from roots of Bauhinia variegata linn were investigated for their anthelmintic activity by using three concentrations (10, 25, & 50mg/ml) as test worms. Results  were  expressed  in  terms  of  time  of  paralysis  and  time  of death of worms and the activity was compared with albendazole as reference standard & Normal saline served as control. Dose dependent decreased paralyzing time and death time was observed. The results of present study indicated that crude methanolic root extract significantly demonstrated paralysis and also caused death of worms especially at higher concentration of (50 mg/ml), Bauhinia variegata showed the best anthelmintic activity. The use of the roots as anthelmintic has been established and further studies are recommended to isolate the active principles answerable for the activity.